The Wage Effects of Job Polarization: Evidence from the Allocation of Talents - Michael Böhm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Over the last decades, the United States and other developed countries have experienced profound job polarization whereby employment in high-skill and low-skill occupations increased at the expense of employment in middle-skill occupations. This paper examines the wage effects of job polarization: first, have the relative wages of workers in middle-skill occupations declined as the prevalent demand-side explanation for job polarization predicts? Second, has the relative price paid per unit of effective labor in the middle-skill occupations dropped with polarization? Third, can job polarization explain the changes in the overall wage distribution over that time period? I answer these questions by comparing over time two representative cohorts of young workers in the United States for whom I can consistently measure relative skills in occupations. My results show that the answer to the first two questions is yes while the answer to the third question is partly yes and partly inconclusive.
Keywords: J21; J23; J24; 330